Preferences for the future of the Southport Spit: evidence from a choice experiment. Issue 4 (1st October 2020) - Graham, Victoria; Fleming, Christopher M.; Agimass, Fitalew; Smart, James C. R.
ABSTRACT: The Southport Spit, an undeveloped open space at the northern end of the Gold Coast beaches, has been subject to contentious development proposals. This study employs a choice experiment to elicit residents' preferences for the future of the Spit in terms of development focus, maximum permitted height of development and extent of developed space. From an online choice experiment survey, we estimate a latent class model that reveals two strongly opposing viewpoints and a third, more nuanced, viewpoint. A pro-conservation segment opposes development of either a cruise ship terminal or casino, prefers low-rise development and opposes any increase in the extent of developed space. In contrast, a pro-development segment favours building a cruise ship terminal, a casino, or both a cruise ship terminal and a casino, prefers medium-rise development and has no clear preferences for how much of the available footprint should be developed. This study contributes to the small body of literature employing choice experiments to elicit the land-use preferences of urban communities; findings may help to explain why, to date, so little progress has been made towards reaching consensus on the future of the Spit.